ANALISIS TINGKAT KEPUASAN NELAYAN TERHADAP FASILITAS PELAYANAN DI PANGKALAN PENDARATAN IKAN (PPI) MANGGAR BARU KOTA BALIKPAPAN - Dicky Prikandhany; Fitriyana Fitriyana (Universitas Mataram, 2026)
The Fish Landing Base (PPI) plays a crucial role as a logistics hub and primary service provider for small-scale fishermen in Indonesia. Amid the demands of economic development and the strategic role of Balikpapan City as the gateway to the National Capital (IKN), the performance of PPI Manggar Baru must be effectively assessed to ensure optimal support for the local fisheries sector. This study aims to measure the satisfaction level of fishermen using PPI Manggar Baru and identify priorities for facility improvements. The method used is descriptive quantitative through surveys involving fishermen who use the PPI Manggar Baru services. The data were analyzed using two main techniques: the Customer Satisfaction Index (CSI) to determine the overall satisfaction index by mapping the gap between expectations (importance) and performance (reality). The analysis results show that the CSI for PPI Manggar Baru is 69.70%, indicating that the satisfaction level of fishermen falls into the